Subsurface Lithology Analysis Using HVSR Method in Jorong Ranah, X Koto Singkarak District - Althaf, Muhammad Mahdy; Syafriani, Syafriani; Zulhendra, Harman Amir (Mataram University, 2025)
Jorong Ranah bordered Sumani segment and the Sianok segment. Both of these segments had experienced demaging earthquakes that affected Jorong Ranah. The damage caused could be determined by analyzing the subsurface lithology. This study aimed to determine the value of dominant frequency (f0) and amplification factor (A0) as well as the shear wave velocity (Vs) and subsurface lithology. Microtremor research was conducted at 8 measurement points. Microtremor signals were analyzed using the HVSR method to obtain data in the form of f0 and A0 presented in the form of H/V curves. The values were analyzed using Easy HVSR software to obtain a curve of shear wave velocity values against depth. 2D modeling of subsurface lithology was conducted using Rockworks software. The results showed that the f0 value in Jorong Ranah ranged from 1.25 - 14.75 Hz and the A0 value ranged from 3.26 - 6.92. The shear wave velocity (Vs) values ranged from 100 m/s - 1,604 m/s at depths ranging from 0 - 116.67 meters. In the first layer, the dominating subsurface lithologies were silt, hard sandy loam, breccia tuff, red soil, and gracefully sandstone. In the second layer, the dominating subsurface lithologies were silt, hard sandy loam, tuff, and volcanic breccia. In the third layer, the dominating subsurface lithologies were red soil, volcanic breccia, tuff, and tuff breccia. And in the fourth layer, the dominating subsurface lithologies were red soil and tuff breccia. Subsurface lithology affected potential damage, with high shear wave velocity (Vs) indicating stable, dense rocks and lower damage potential, while low Vs values suggested soft rocks that were more prone to deformation and higher damage risk.